hnRNPA2B1 Promotes Colon Cancer Progression via the MAPK Pathway - Tang, Jingzhi; Chen, Zhimin; Wang, Qi; Hao, Weijie; Gao, Wei-Qiang; Xu, Huiming (Frontiers in Genetics, 2021)
HNRNPA2B1, an RNA-binding protein, plays a key role in primary microRNA processing, alternative splicing, mRNA metabolism and transport. Interestingly, hnRNPA2B1 also works as an N6-methyladenosine (m6A) reader and is critical during tumorigenesis of various tissue types. However, its role in colon cancer is still unclear. In this study, we aimed to elucidate the biological functions of hnRNPA2B1 and to explore its underlying mechanisms in colon cancer. We examined the expression of hnRNPA2B1 in Oncomine and TCGA databases. Then verified the findings in colon cancer cells and clinical samples with western blotting and immunohistochemistry (IHC). We used CRISPR/Cas9 directed gene editing to knockout hnRNPA2B1 expression in human colon cancer cell line SW480 and HCT-116 and carried out both in vivo and in vitro experiments. The results were further confirmed by RNA-seq analyses. We found that hnRNPA2B1 significantly promoted colon cancer cell proliferation both in vitro and in vivo, while knockout of hnRNPA2B1 induced apoptosis and cell cycle arrest in SW480. RNA-seq analyses revealed that the ERK/MAPK pathway was activated by hnRNPA2B1 upregulation. In addition, both hnRNPA2B1 and MAPK pathway were activated in clinical colon cancer specimens and positively correlated. Mechanistically, hnRNPA2B1 appeared to be an upstream regulator of the ERK/MAPK pathway and inhibition of MAPK signaling blocked the effects of hnRNPA2B1. Taken together, our data demonstrated that the RNA-binding protein hnRNPA2B1 promotes cell proliferation and regulates cell cycle and apoptosis of human colon cancer by activating the ERK/MAPK signaling, which may provide a new insight into the development of hnRNPA2B1 as a potential therapeutic target for treatment of colon cancer.